2019
DOI: 10.1088/1757-899x/629/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Finite element study of tunable cantilever plate structure using position change

Abstract: In this paper, a tunable cantilever plate structure is presented, in which a box is attached to each corner of its free sides and a ball is placed in each box. Change of the balls position makes natural frequency of the structure variable, which expands working bandwidth of the structure to accommodate the complex ambient vibration. The modal analysis of the tunable cantilever plate is carried out by the finite element software-ABAQUS. Changing the balls position, it is found that there are maximum and minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Reference [33] designed an auto-tuning instrument by attaching a box with two cylinders based on a cantilever beam structure, and did not further study the relationship between position and frequency/bandwidth. In 2019, Chen et al [34,35] proposed a tunable cantilever plate attaching a box at each corner of the free end and placing a ball in each box. It is found that the natural frequency of the structure changes between the maximum (f max ) and the minimum natural frequency (f min ) when the ball position changes in the box.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Reference [33] designed an auto-tuning instrument by attaching a box with two cylinders based on a cantilever beam structure, and did not further study the relationship between position and frequency/bandwidth. In 2019, Chen et al [34,35] proposed a tunable cantilever plate attaching a box at each corner of the free end and placing a ball in each box. It is found that the natural frequency of the structure changes between the maximum (f max ) and the minimum natural frequency (f min ) when the ball position changes in the box.…”
mentioning
confidence: 99%
“…Therefore, the position of two balls is easier to be adjusted without colliding and squeezing each other, which is conducive to realize the auto-tuning function in a broad-frequency vibration environment. In this paper, hammering experiments are performed to verify the effect of the balls position on the natural frequency and the theoretical bandwidth, and to compare with the theoretical [35] and finite element results [34]. The stronger Hammer experiment.…”
mentioning
confidence: 99%
See 3 more Smart Citations